Business analysis - Paul, Debra; Cadle, James (BCS, The Chartered Institute for IT, 2020)
All organisations need to respond to the challenges within the highly competitive global economy; business analysts are at the forefront of these responses. The 4th edition of this bestselling book provides a comprehensive guide for business analysts, encompassing the key concepts, frameworks & techniques needed to provide professional BA services.
Keywords: System analysis.; Management information systems.; Organizational effectiveness.; elektronické knihy; electronic books